Internal and external factors on stock returns: evidence from the Indonesia Stock Exchange - Tahmat Tahmat; Imelda Melindyana; Fitria Lilyana; Suharjanta Wisnu Pitara; Inayati Nasrudin (International Journal of Indonesian Business Review, 2026)
Stock return is a consideration for investors when making investment decisions. Investors can observe the level of stock return through internal and external factors of the company in order to maximize profits. This study aims to determine the macroeconomic effect as measured by inflation, interest rates, world oil, exchange rate, and company financial performance as measured by the debt-to-equity ratio, debt-to-asset ratio, return on equity, and earnings per share on return in the LQ45 stock group on the Indonesia Stock Exchange for the period 2011–2022. The population in this study was 45; based on the purposive sampling technique, we obtained a sample of 15 companies. This type of research is quantitative with secondary data; the method used is panel data regression analysis using the Common Effect Model approach. The results of the F test found that inflation, interest rates, world oil, exchange rate, debt-to-equity ratio, debt-to-asset ratio, return on equity, and earnings per share simultaneously have a significant effect on stock returns. Based on the t test, it was found in the study that inflation has a negative and significant effect on stock returns, the exchange rate has a negative and significant effect on stock returns, the debt-to ratio has a positive and significant effect on stock returns, and interest rates, such as world oil, debt-to-asset ratio, return on equity, and earnings per share, have no effect on stock returns.